1998
DOI: 10.1083/jcb.143.7.1899
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Melanosome Dynamics within Wild-Type and Dilute Melanocytes Suggests a Paradigm for Myosin V Function In Vivo

Abstract: Unlike wild-type mouse melanocytes, where melanosomes are concentrated in dendrites and dendritic tips, melanosomes in dilute (myosin Va−) melanocytes are concentrated in the cell center. Here we sought to define the role that myosin Va plays in melanosome transport and distribution. Actin filaments that comprise a cortical shell running the length of the dendrite were found to exhibit a random orientation, suggesting that myosin Va could drive the outward spreading of melanosomes by catalyzing random walks. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
514
4
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(559 citation statements)
references
References 48 publications
33
514
4
8
Order By: Relevance
“…First, by expressing myosin Va tail domain-GFP fusion proteins in wild-type melanocytes, displacing endogenous myosin Va from the melanosomes, melanosomes redistributed on microtubules to the cell center, creating a dominant-negative dilute-like phenotype. By comparing the dynamics of melanosomes in microtubule-depleted wild-type and dilute melanocytes, a class of slow ( 0.14 mm/s) myosin Va-dependent (short range) in vivo melanosome movements was identified (10). Recently direct interactions could be demonstrated between microtubule-associated and actin-associated motor proteins (37), supporting their interactive way of co-operation.…”
Section: Motor Protein Complexes: a Newer Concept Of Melanosome Movementmentioning
confidence: 98%
See 1 more Smart Citation
“…First, by expressing myosin Va tail domain-GFP fusion proteins in wild-type melanocytes, displacing endogenous myosin Va from the melanosomes, melanosomes redistributed on microtubules to the cell center, creating a dominant-negative dilute-like phenotype. By comparing the dynamics of melanosomes in microtubule-depleted wild-type and dilute melanocytes, a class of slow ( 0.14 mm/s) myosin Va-dependent (short range) in vivo melanosome movements was identified (10). Recently direct interactions could be demonstrated between microtubule-associated and actin-associated motor proteins (37), supporting their interactive way of co-operation.…”
Section: Motor Protein Complexes: a Newer Concept Of Melanosome Movementmentioning
confidence: 98%
“…once the melanosomes reach this subcortical area, is an emerging field of research. Overexpression of green fluorescent protein (GFP)-tagged myosin Va-tail domain fusion proteins shows colocalization with black end-stage melanosomes, indicating that indeed this tail domain is the cargo-binding domain, and moreover, induces a dilute-like dominant-negative image of perinuclear melanosome accumulation through competition with native myosin Va for the melanosome cargo (10,12). These experiments also revealed that, in melanoma cells, myosin Va also colocalizes with, e.g.…”
Section: Myosin Va the First Candidate Genementioning
confidence: 99%
“…Although melanosomes are transported along both actin-based and microtubule-based motors in wild-type melanocytes, these mutations affect the actin-based movements only. The bidirectional microtubule-based movements between the center of the cell and its periphery still take place in mutant melanocytes, but a failure in melanosome capture at the periphery results in their accumulation at the center (Wu et al, 1998). The d, ash, and ln loci encode for the Myosin Va, Rab27a and Melanophilin proteins, respectively (Mercer et al, 1991;Wilson et al, 2000;Matesic et al, 2001).…”
Section: Melanosome Transportmentioning
confidence: 99%
“…In mammalian cells, myosin V motors have been implicated in transporting melanosomes (Wu et al, 1998), recycling endosomes (Lapierre et al, 2001), and the endoplasmic reticulum (Wagner et al, 2011). To perform these functions, all myosin V motors consist of two heavy chains with N-terminal motors dimerizing along a coiledcoil stalk, six associated light chains decorating each forcetransducing lever arm, and two cargo-binding globular tail domains at the C terminus (Hammer and Sellers, 2012).…”
Section: Introductionmentioning
confidence: 99%